2008
DOI: 10.1196/annals.1428.082
|View full text |Cite
|
Sign up to set email alerts
|

The Application of PCR and Reverse Line Blot Hybridization to Detect Arthropod‐borne Hemopathogens of Dogs and Cats in Trinidad

Abstract: Arthropod-borne diseases are important causes of morbidity and mortality of companion animals in Trinidad. As clinical signs are vague, more sensitive methods to diagnose these diseases based on the polymerase chain reaction (PCR) followed by reverse line blot hybridization (RLB) of amplified products are being developed. An RLB of 14 oligonucleotide probes coupled with polymerase chain-amplified regions of 16S rRNA or 18S rRNA genes of hemoparasites from cats and dogs detected Ehrlichia canis, Anaplasma platy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 14 publications
2
31
0
1
Order By: Relevance
“…Feline piroplasmosis is associated with anorexia, weight loss, gastrointestinal alterations, anemia, thrombocytopenia, leukocytosis or leukopenia, and jaundice (Criado-Fornelio, 2012a; Vilhena et al, 2013). Our findings also emphasize the occurrence of B. vogeli, a canid piroplasmid, in cats in Brazil, corroborating with previous studies conducted in Brazil others regions of the world (Georges et al, 2008;Simking et al, 2010;Vilhena et al, 2013). Additionally, the present work highlights the diversity of piroplasmids circulating in cats in Brazil and the need for molecular confirmation of piroplasmas found in erythrocytes of cats' blood smears.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Feline piroplasmosis is associated with anorexia, weight loss, gastrointestinal alterations, anemia, thrombocytopenia, leukocytosis or leukopenia, and jaundice (Criado-Fornelio, 2012a; Vilhena et al, 2013). Our findings also emphasize the occurrence of B. vogeli, a canid piroplasmid, in cats in Brazil, corroborating with previous studies conducted in Brazil others regions of the world (Georges et al, 2008;Simking et al, 2010;Vilhena et al, 2013). Additionally, the present work highlights the diversity of piroplasmids circulating in cats in Brazil and the need for molecular confirmation of piroplasmas found in erythrocytes of cats' blood smears.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, B. vogeli was detected in blood samples from stray domestic cats in a Brazilian zoo . Also, B. vogeli DNA has already been detected in cat's blood samples from Trinidad (Georges et al, 2008), Thailand (Simking et al, 2010) and Portugal (Vilhena et al, 2013). André et al (2011) reported the detection of Babesia spp.…”
Section: Discussionmentioning
confidence: 95%
“…No entanto, contrariando os resultados deste estudo, alguns autores obtiveram sucesso na ampliϐicação de DNA de Ehrlichia spp. em gatos domésticos (Beauϐils et al 2002, Yin-Chiachun et al 2003, Oliveira 2008, Tabar et al 2008, Georges et al 2008) e em felinos selvagens onde André (2008) foi o pioneiro a detectar a presença de E. canis em 11 felinos selvagens mantidos em zoológicos de São Paulo e Brasília. Breitschwerdt et al (2002) Após testar a nested PCR com primers baseados na seqüência do gene 16SrRNA da Ehrlichia spp.…”
Section: Methodsunclassified
“…However, E. canis DNA has been detected in blood of domestic cats in North America (2) and recently in Trinidad by reverse line blot hybridization (13). Moreover, experimental infection of cats by Neorickettsia risticii (formerly Ehrlichia risticii) has been described (8).…”
mentioning
confidence: 99%
“…Blood-borne pathogens in domestic cats have been attracting the attention of researchers (11,27,13,28). With the use of molecular tools, a large number of pathogens previously recognized only as parasites of dogs have also been detected in domestic cats (2,25).…”
mentioning
confidence: 99%